DBA/1 mice display equivalent cardiac function to C57BL/6J mice. Issue 4 (16th February 2021) - Wang, Zhen; Zhou, Zhengwei; Guo, Paipai; Wang, Manman; Sun, Hanfei; Tai, Yu; Xiao, Feng; Han, Yongsheng; Wei, Wei; Wang, Qingtong
Abstract : New Findings: What is the central question of this study? Do normal adult DBA/1 mice have cardiac function and performance equal to those of C57BL/6J mice? What is the main finding and its importance? Male adult DBA/1 mice show equivalent cardiac function to C57BL/6J mice up to 8 months old. Therefore, cardiac dysfunction could be investigated in an autoimmune diseases model established with DBA/1 mice. Abstract: Cardiovascular mortality has been increasing, and in particular, cardiovascular damage caused by some chronic autoimmune diseases accounts for a large proportion of this. C57BL/6J mice have been used mostly in studies of cardiovascular diseases. However, for purposes of modelling, this strain of mouse has a very low incidence of some chronic immune diseases such as rheumatoid arthritis, to which instead DBA/1 mice are more susceptible. Basic cardiac function differs between mice with different genetic backgrounds. Therefore, we monitored cardiac function and structure of normal male C57BL/6J and DBA/1 mice for six consecutive months. Echocardiography was used to monitor cardiac functions once a month and cardiac systolic function was measured upon isoproterenol challenge at the end of observation. The Excitation–contraction coupling‐related proteins were measured by western blotting. Heart tissue sections were subject to haematoxylin–eosin, TUNEL and Alizarin red staining. The results demonstrated that systolic and diastolic function did not vary significantly and both strains were indistinguishable in appearance and structure of hearts. DBA/1 mice showed a good cardiac β‐adrenergic response comparable to C57BL/6J mice with isoproterenol treatment. The phosphorylation of phospholamban at either its protein kinase A or its Ca 2+ /calmodulin‐dependent protein kinase II site, as well as the activation of troponin I showed no significant difference between strains. These findings suggested that there was no obvious difference in the heart structure and function of normal male DBA/1 mice compared with C57BL/6J mice. The DBA/1 mouse is a strain applicable to investigating autoimmune disease‐induced heart dysfunction and exploring potential interventions. Abstract :